A IMPORTÂNCIA DO MONITORAMENTO DA QUALIDADE DA ÁGUA DOS CORPOS HÍDRICOS DO MUNICÍPIO DE DOURADOS/MS - SANTINI, Adriano Cesar; CARVALHO, Laércio Alves de; GALBETTI, Marcus Vinicius (ANAIS DO ENIC, 2018)
-